UJI EFEKTIFITAS NEMATODA ENTOMOPATOGEN SEBAGAI PENGENDALI PENGGEREK PUCUK KELAPA SAWIT (Oryctes rhinoceros L.) (Coleoptera: Scarabaidae) DI LABORATORIUM - Selly Khairunnisa; Mukhtar Iskandar Pinem; Fatimah Zahara (Jurnal Agroekoteknologi, 2014)
Efficacy Test of Entomopathogenic Nematodes as a Controll of Coconut Palm Beetle (Oryctesrhinoceros L.) (Coleoptera : Scarabaidae) in the Laboratory. This research was conducted todetermine the effectiveness of entomopathogenic nematodes. as a controll of O. rhinoceros L.(Coleoptera : Scarabidae) in the Laboratory. This research was carried out in the Laboratoryof Pests and Laboratory of Plant Diseases, Agroecotechnology, Faculty of Agriculture, Universityof North Sumatra from January to March 2013. The method of this research was CompletelyRandomized Design (CRD) non-Factorial which consist of 6 treatments and 3 replications.Treatments being tested were 6 levels of population density Infective Juvenile (JI) of nematodesentomopathogenic (0, 50, 100, 150, 200, 250 JI/ml). The results of this research showed that withpopulation density of nematodes entomopathogenic 200 JI/ml and 250 JI/ml at 144 hours after theapplication is effective for controlling larva mortality O. rhinoceros L. for 85,71% and 100%.The fastest ’s larval mortality time was found with population density of nematodesentomopathogenic 250 JI/ml at 24 hours after the application.Keywords: Oryctes rhinoceros L., oil palm, entomopathogenic nematodes